2011
DOI: 10.1089/sur.2010.035
|View full text |Cite
|
Sign up to set email alerts
|

Steroids in the Treatment of Group A Streptococcal Necrotizing Soft Tissue Infection

Abstract: The cases illustrate the possible utility of high-dose steroids in the treatment of this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Lack of glove use while caring for index patient; presence of dermatitis on affected skin Sablier et al 8 GAS necrotizing fasciitis 1 (necrotizing fasciitis) Transmission related to sharps injury incurred during initial debridement of index patient This study 1 GAS necrotizing fasciitis 2 (1 with necrotizing fasciitis with toxic shock syndrome, 1 with pharyngitis)…”
Section: Intraoperative Patient-to-healthcare-worker Transmission Of mentioning
confidence: 90%
See 2 more Smart Citations
“…Lack of glove use while caring for index patient; presence of dermatitis on affected skin Sablier et al 8 GAS necrotizing fasciitis 1 (necrotizing fasciitis) Transmission related to sharps injury incurred during initial debridement of index patient This study 1 GAS necrotizing fasciitis 2 (1 with necrotizing fasciitis with toxic shock syndrome, 1 with pharyngitis)…”
Section: Intraoperative Patient-to-healthcare-worker Transmission Of mentioning
confidence: 90%
“…In June 2009, an extensive debridement of both lower extremities was performed on a 55-year-old patient with necrotizing fasciitis and myonecrosis following blunt injury (day 1), as reported previously. 1 The patient presented with septic shock and required urgent operative debridement and hip disarticulation. Blood and wound cultures grew Streptococcus pyogenes.…”
Section: Intraoperative Patient-to-healthcare-worker Transmission Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus pyogenes is a β-hemolytic group A streptococcus [230] , a human pathogen [165] , [231] , which causes puerperal sepsis [232] , tonsillitis [233] , toxic shock syndrome [234] , [235] , and necrotizing fasciitis [236] , [237] .…”
Section: Production Of Ha With Streptococcimentioning
confidence: 99%
“…35 Corticosteroids have a similar, albeit less specific effect on the immune response to bacterial toxins have been used as an adjunct in patients with NSTI and toxic shock syndrome. 38 Hyperbaric oxygen treatment is theorized to aid in the prevention of the progression of tissue loss and therefore morbidity and mortality. However, in a Cochrane review, no literature worth of analysis was found, and no summation of data was suggested.…”
Section: Adjunctsmentioning
confidence: 99%